Sports Orthopedics - Kleinert J; 5; Kellmann M; 3; Hasenbring MI; Belz J; Heidari J; Levenig C; Gawlik A (Dynamic Media Sales Verlag, 2018)
Psychosocial interventions for back pain patients are well established elements of treatment regimens and numerous reviews support their effectiveness. Research is sparse regarding the specific case of elite athletes suffering from back pain(BP), and the effects of psychological treatments in this population. Therefore, based on a biopsychosocial paradigm, this article describes four intervention approaches with a specific orientation towards athletes 1) pain perception and pain management, 2) body experience and body concept, 3) motivation and self-regulation, and 4) stress management and recovery. For each of these four topics, a short overview of the key research and existing interventions is given. Based on the overviews of these four topics, specific treatments that have been developed by the authors are described. These treatments particularly aim 1) to gradually increase physical and social activity while reducing BP and disability, 2) to concentrate on positive aspects of body experience, 3) to enhance patients self-efficacy and intrinsic motivation for rehabilitation and 4) to promote and monitor individual recovery activities,and relaxation techniques. Evidence concerning the effects and feasibility of these developments is expected from current intervention studies. Future studies are encouraged to examine whether the developed interventions are also effective when offered by trained physiotherapists or physicians in primary care. KEY WORDS: Back Pain, Elite Sport, Pain Coping, Body Concept, Motivation, Recovery